طريقة ابن عبد السلام الهواري المالكي في تقرير مسائل الحج والصيد في كتابه تنبيه الطالب - Lutfi Firdaus Munawar (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to reveal the technical and scientific methods used by Ibn `Abd al-Salām al-Hawwārī al-Mālikī in explaining the problems of hajj and hunting in his book, Tanbīh al-Ṭālib, and to explain its benefits for the scientific treasures of the Maliki school of jurisprudence and Islamic jurisprudence in general. This study uses the al-waṣfi method in the tamhīid section and the istiqra' istintaji method in the discussion section on Ibn `Abd al-Salām's method in explaining the problems of hajj and hunting, namely by perusing all chapters of hajj and hunting and then concluding the method used by the author. Among the results of this research are: first, this paper has succeeded in uncovering several scientific methods used by the author in explaining the chapters of pilgrimage and hunting; secondly, the author has made a valuable contribution to the Maliki school of thought in terms of knowledge and methods of writing book syarahs; third, there is a serious effort from the author in making syarah on the issues of pilgrimage and hunting, this is evident from the use of many methods and ways of doing so; fourth, there is a strong commitment from the author to always present arguments from texts and others, also always present a discussion of the problems discussed by presenting rebuttals and answers; fifth, the author's specialty lies in his strength in strengthening (tarjih) problems by always including satisfying arguments.